America, the Vietnam War, and the world : comparative and international perspectives - Daum, Andreas W.; Gardner, Lloyd C., 1934-; Mausbach, Wilfried, 1964- (German Historical Institute ; Cambridge University Press, 2003)
This book presents new perspectives on the Vietnam War, its global repercussions, and the role of this war in modern history. The volume revels "America's War" as an international event that reverberated all over the world: in domestic settings of numerous nation-states, combatants and noncombatants alike, as well as in transnational relations and alliance systems. The volume thereby covers a wide geographical range - from Berkely and Berlinto Cambodia and Canberra. [In the book], 'America's War' is thus depicted as a truly global event whose origins and characteristics deserve an interdisciplinary treatment.